Optimizing Talent Management Practices: a Case Study of PT X’S Head Office in Indonesia’s Forestry Sector - Anisa Irbah; Andika Putra Pratama (KOLONI, 2026)
Structural inequality in talent management is increasingly recognized as a systemic barrier to organizational sustainability, particularly in industries operating in geographically dispersed and socially diverse environments. This study examines how the implementation of structural equity inthe talent management cycle—encompassing recruitment, placement, career development, promotion, and succession planning—is appliedat a company in the forestry sector. Using a qualitative case study approach, data were collected through in-depth interviews with elevenkey informants from various organizational levels, supplemented by document analysis and field observations. The findings reveal that structuralequity has not been fully realized, stemming from the absence of an integrated Human Resources Information System (HRIS) and a lack of formalized career paths. These conditions result in unequal access to career development opportunities, perpetuate a cycle of talent stagnation, and impact long-term workforce sustainability. Based on Strategic Human Resource Management (SHRM), organizational justice theory,and stakeholder theory, this study proposes a three-phase intervention framework centered on equity: (1) implementation of an integratedHRIS as a data foundation, (2) establishment of individual KPIs and a formalized career path structure, and (3) development of structured communication mechanisms and a culture of transparency. These findings contribute to the scholarly discourse on equity in HRM within the context of organizations operating in resource -intensive sectors.